EFEKTIVITAS PELAYANAN PERIZINAN BERBASIS TEKNOLOGI TENTANG PELAYANAN PERIZINAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN TULANG BAWANG - Agustuti Handayani; Tara Larasati (e-JKPP, 2021)
This study mainly wants to examine (1) How Effectiveness of Technology- Based Licensing Services is About Licensing Services in Tulang Bawang Regency, (2) What aspects support and hinder the Effectiveness of Technology-Based Licensing Services regarding Licensing Services in Tulang Bawang Regency.This research design uses qualitative research with qualitative descriptive analysis method. The research design aims to describe and analyze qualitatively the Effectiveness of Technology-Based Licensing Services About Licensing Services in Tulang Bawang Regency.The results of the study indicate that the effectiveness of technology-based licensing services regarding licensing services in Tulang Bawang Regency has been running, but not optimal, this is because it has not been supported by an inadequate level of education of the apparatus, according to the dimensions, namely (1). The unit of time is relatively not optimal because of the limited work infrastructure, so it is not yet able to provide timely services, (2) The unit of results, is not optimal because there are often people who are late due to frequent power outages, (3) the quality of work is still not optimal by service providers. officer